Diary of a National Scout. P. J. du Toit 1900-1902. - Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2011)
This book is the second in the new series of works edited and published by the Institute for Historical Research of the Human Sciences Research Council under direction of Dr C. M. Bakkes. The first book, Die Dagboek van H. C. Bredell, cast new light on President Kruger's years in exile; in the new publication some insight is given into the tensions and struggles in the mind of the writer, who orginally fought with the Boers but later went over to the British and actively supported them as a National Scout.